ANALISIS PERMINTAAN JASA ANGKUTAN BUS TRAYEK MAKASSAR – WATAMPONE VIA CAMBA - Marniati Syam (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
The aim of the study was to discover the effect of family income, travel expenses, duration of travel, convenience, and travel management on demand of bus transportation from Makassar to Watampone via Camba.         The data of this study were collected through structured interview and questionnaire and analyzed by using logistic regression model. The selection of samples was done by accidental sampling.            The results of the study indicate that the family income and duration of travel have positive and significant correlation with the demand of bus transportation service from Makassar to Watampone via Camba. The travel expenses and conveniences have a negative and insignificant correlation with the demand of bus transportation service, whereas travel management has a positive and significant correlation with the demand of bus transportation service. The travel management has a positive but insignificant correlation with the demand of bus transportation service.Keyword : Transportation service, demand